STRATEGI THINK-TALK-WRITE (TTW) UNTUK MENINGKATKAN KEMAMPUAN MENULIS SISWA - Angella Novitaningrum; Zuhria Agustin (PPPM STIT MIFTAHUL MIDAD, 2024)
This study was intended to analyze the use of Think-Talk-Write (TTW) strategy to enhance students' writing ability along with its benefits and challenges. It used descriptive qualitative as a research design. The subjects of this study were the fourth semester of English Department students at STIT Miftahul Midad Lumajang. Observation and semi-structured interview were conducted in order to collect data. The findings revealed that there were seven procedures of TTW strategy which employed by lecturer in the writing process. Further, students perceived the use of TTW strategy positively. They argued that it could improve communication and collaboration skills, enhance critical thinking abilities, increase confidence in expressing ideas, increase deeper understanding of writing principles, and heighten engagement in the writing process. However, they also encountered some challenges such as the difficulties in organizing thoughts, navigating group discussions, managing time constraints, and maintaining coherence in written compositions. Overall, the findings of this research contribute valuable insights into the implementation of TTW strategy and its impact on students learning experiences. By addressing the challenges identified in the study and leveraging theoretical frameworks to inform instructional practices, educators can enhance the effectiveness of TTW as a learning strategy and support students in developing essential cognitive and metacognitive skills.